TGMS in Rapeseed (Brassica napus) Resulted in Aberrant Transcriptional Regulation, Asynchronous Microsporocyte Meiosis, Defective Tapetum, and Fused Sexine - Liu, Xi-Qiong; Liu, Zhi-Quan; Yu, Cheng-Yu; Dong, Jun-Gang; Hu, Sheng-Wu; Xu, Ai-Xia (Frontiers in Plant Science, 2017)
The thermo-sensitive genic male sterility (TGMS) line SP2S is a spontaneous rapeseed mutation with several traits that are favourable for the production of two-line hybrids. To uncover the key cellular events and genetic regulation associated with TGMS expression, a combined study using cytological observation, transcriptome profiling, and gene expression analysis was conducted for SP2S and its near-isogenic line SP2F grown under warm conditions. Asynchronous microsporocyte meiosis and abnormal tapetal plastids and elaioplasts were demonstrated in the anther of SP2S. The tetrad microspore did not undergo mitosis before the cytoplasm degenerated. Delayed degradation of the tetrad wall, which led to tetrad microspore aggregation, resulted in postponement of sexine (outer layer of pollen exine) formation and sexine fusion in the tetrad. The nexine (foot layer of exine) was also absent. The delay of tetrad wall degradation and abnormality of the exine structure suggested that the defective tapetum lost important functions. Based on transcriptomic comparisons between young flower buds of SP2S and SP2F plants, a total of 465 differentially expressed transcripts (DETs) were identified, including 303 up-regulated DETs and 162 down-regulated DETs in SP2S. Several genes encoding small RNA degrading nuclease 2, small RNA 2'-O-methyltransferase, thioredoxin reductase 2, regulatory subunit A alpha isoform of serine/threonine-protein phosphatase 2A, glycine rich protein 1A, transcription factor bHLH25, leucine-rich repeat receptor kinase At3g14840 like, and fasciclin-like arabinogalactan proteins FLA19 and FLA20 were greatly depressed in SP2S. Interestingly, a POLLENLESS3-LIKE 2 gene encoding the Arabidopsis MS5 homologous protein, which is necessary for microsporocyte meiosis, was down-regulated in SP2S. Other genes that were up-regulated in SP2S encoded glucanase A6, ethylene-responsive transcription factor 1A-like, pollen-specific SF3, stress-associated endoplasmic reticulum protein 2, WRKY transcription factors and pentatricopeptide repeat (PPR) protein At1g07590. The tapetum-development-related genes, including BnEMS1, BnDYT1, and BnAMS, were slightly up-regulated in 3-mm-long flower buds or their anthers, and their downstream genes, BnMS1 and BnMYB80, which affect callose dissolution and exine formation, were greatly up-regulated in SP2S. This aberrant genetic regulation corresponded well with the cytological abnormalities. The results suggested that expression of TGMS associates with complex transcriptional regulation.